2017
DOI: 10.1007/s00428-017-2144-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of intraductal papillary neoplasms of the bile duct: a comparison with intraductal papillary mucinous neoplasm of the pancreas with reference to subtypes

Abstract: Intraductal papillary epithelial neoplasms of the pancreatobiliary system (intraductal papillary neoplasm of the bile duct (IPNB) and intraductal papillary mucinous neoplasm (IPMN)) seem to share many clinicopathological features; however, IPNB has not been fully characterized. In order to understand the clinicopathological/immunohistochemical features of IPNB better, we compared 52 cases of IPNB with 42 cases of IPMNs with mural nodules. The IPNB cases were divided into two groups according to their histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 24 publications
2
35
1
Order By: Relevance
“…However, according to the current WHO Classification, and based on MUC IHC, the gastric microbiopsy specimens from our study would be misclassified as PB, even though all lesions showed low‐grade dysplasia. Recent articles and reviews quote the WHO classification or use identical anti‐tumor MUC1 antibodies with no reflection on this . Analyzing the five studies quoted in the WHO classification, three use an antibody with specificity against MUC1 core (DF3 or Ma552) , while the rest use an anti‐sialylated MUC1 antibody .…”
Section: Resultsmentioning
confidence: 99%
“…However, according to the current WHO Classification, and based on MUC IHC, the gastric microbiopsy specimens from our study would be misclassified as PB, even though all lesions showed low‐grade dysplasia. Recent articles and reviews quote the WHO classification or use identical anti‐tumor MUC1 antibodies with no reflection on this . Analyzing the five studies quoted in the WHO classification, three use an antibody with specificity against MUC1 core (DF3 or Ma552) , while the rest use an anti‐sialylated MUC1 antibody .…”
Section: Resultsmentioning
confidence: 99%
“…They can both secrete mucus and cause corresponding blockages in the ducts. Most importantly, they are precancerous lesions [3]. In recent years, IPMN-P has been gradually recognized, but the understanding of IPMN-B is just the beginning.…”
Section: Discussionmentioning
confidence: 99%
“…The disease can occur in both intrahepatic and extrahepatic bile ducts, which are connected with bile ducts. About 1/3 of IPNB can secrete mucus, which is called intraductal papillary mucinous tumor of the bile ducts (IPMN-B) [2,3]. At present, the description of IPMN-B is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, consistency of histological definition has not been observed, and the controversy of diagnosis is still referred to by clinical physicians and pathologists (11,21,23) Therefore, the clinical aspect of preoperative histological diagnosis and surgical indication has not yet been fully clarified. Our previous reports identified the various tumor morphologies of IPNB, good prognosis, and difficulty in comparison with similar biliary tumors (19,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the patients with IPNB did not show any solid mass lesion detected by conventional imaging examination. The follow-up strategy was clearly defined in IPMN of the pancreas, which is considered the counterpart disease of IPNB (10,20,23). If the clinical or imaging characteristics indicating low-grade malignancy in some patients with IPNB were clarified, a similar strategy to IPMN would be used.…”
Section: Discussionmentioning
confidence: 99%